Pengaruh Pola Pikir dan Pola Hidup Pasca Covid- 19: Telaah Singkat Ledakan Home Sweet Home Perspektif Rhenald Kasali - Fani Putri Amaliya; Sofiana Saidah; Ahmad Sholikin; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to find out the Effect of Covid-19 on the Environment from Rhenald Kasali's youtube channel entitled